Wind Turbines Control: Features and Trends - Oudah, Ali A.; Izzeldin, I. Mohd; A., Hameed (Canadian Centerof Science and Education, 2014)
Energy is the basis for economic development and it is important to have a reliable supply of energy for the sustainable development of any country. With the rapid growth of the global economy, the energy crisis is aggravating substantially. It is, therefore, of great interest to develop reliable renewable energy resources that can take up a relatively large proportion of the growing energy needs with the crucial feat ures of energy security, environment protection and economic development. Since the beginning of the twenty first century, countries all over the world and international organizations have invested tremendous amount of funds for the development of new energy systems. As a competitor to the conventional energy sources, wind energy is considered to be an important source for a diversified energy portfolio, particularly, because it is a clean energy source with an inexhaustible supply. Wind energy has become one of the fastest growing renewable energy systems with promising prospects for large scale commercialization. We provide in this tutorial paper an overview brief of basic wind turbine energy control systems and an optimistic or reflective area in a recent industry developments and research in wind turbine control systems for more grid performance and frequency stability.